Peste des petits ruminants in Afghanistan - Nikmal Azizi, Ahmad Farid (Kansas State University, 2010)
Peste des petits ruminants (PPR) is an economically important and highly contagious disease of sheep and goats. It is characterized by enteritis, stomatitis, pneumonia, and discharge from the nose and eyes. This report contains a review of PPR and its epidemiology in Afghanistan and other PPR- endemic countries followed by recommendations for dealing disease in Afghanistan. Studies showed that PPR is still endemic in Afghanistan’s neighboring countries including Pakistan, Iran, Tajikistan, and China. From January of 2009 to January of 2010, 852 outbreaks of PPR were reported to the OIE from 24 different countries. However, this study focuses on Afghanistan and some neighboring countries (Iran, Tajikistan). Animal clinics and Veterinary Field Units (VFUs) reported 7,741 cases of PPR from 2008 to 2009 in different parts of Afghanistan. A study by the Food and Agriculture Organization (FAO) in 2009 showed that PPR is endemic in various parts of Afghanistan. Seroprevalence of PPR varied from 0% in Kapisa to 48% in Herat province of Afghanistan. The last chapter of this report includes recommendations and guidelines regarding prevention and eradication of PPR from Afghanistan. These recommendations could help improve animal health and the economy of Afghanistan in the future.
Keywords: Peste des petits ruminants; Afghanistan; Biology, Veterinary Science (0778)